My Grief App for Prolonged Grief in Bereaved Parents: A Pilot Study - Eklund, Rakel; Eisma, Maarten C.; Boelen, Paul A.; Arnberg, Filip K.; Sveen, Josefin (Frontiers in Psychiatry, 2022)
The death of a child is a devastating experience for most parents. Consequently, bereaved parents are at risk to develop physical and mental health problems, including prolonged grief disorder. Nevertheless, there is a lack of evaluated psychosocial interventions for bereaved parents. The primary aim of this study was to examine the feasibility of the My Grief app for bereaved parents. The secondary aim was to evaluate the potential reduction of symptoms of prolonged grief, depression and post-traumatic stress, and cognitive-behavioral processes proposed to prolong grief reactions. The study was a mixed-method open trial design, using pre- and post-intervention surveys and post-intervention interviews. Thirteen parents had access to the app for 4 weeks, eight parents participated in interviews and 10 parents answered the follow-up survey. The study provided evidence for the app's feasibility and acceptability, with participants reporting satisfaction with the app and stating that they would recommend it to parents in similar situations. According to the participants, the app was easy to use, the content gave a feeling of not being alone or weird in how one grieves, and the app gave a valuable overview of information, knowledge and further support. In addition, all parents expressed that an app like My Grief is needed and would be particularly useful to access early in the grieving process. Significant reductions of prolonged grief symptoms (dwithin = 0.86) and grief-related rumination (dwithin = 0.72), loss avoidance (dwithin = 0.95) and negative cognitions (dwithin = 1.36) from pre- to post-assessment were found. In conclusion, the app appears acceptable and feasible to use and will be evaluated in a larger randomized controlled trial (Trial registration number: NCT04552717, https://clinicaltrials.gov/ct2/show/NCT04552717).